Innovation in Indonesian Vocabulary Learning through Interactive PowerPoint Media for Arabic-Speaking Students - Ahsanuddin, Mohammad; Ridwan, Nur Anisah; Ilmi, Fatiya Faza Khabibatul; Prastiwi, Nainisa Nur; Ahsan, Najma Auliya' Maulidah (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Arab students learning Indonesian often struggle to memorize new vocabulary, even though vocabulary is the foundation of language. This challenge is exacerbated by the lack of engaging learning media tailored to everyday contexts. This study aimed to improve students' vocabulary mastery by using interactive PowerPoint slides. Conducting two cycles, the Classroom Action Research (CAR) involved participants from the Indonesian Language and Literature (BIPA) class at Malang State University to assess the impact of this new medium. The instruments used included written tests, direct observation, questionnaires, and other supporting documents. The final analysis revealed significant results: the average score jumped from 56.2 in the pre-test to 78.6 in the post-test in the second cycle, and the completion rate increased from 40% to 88%. Students responded positively, reporting that interactive PowerPoint slides increased motivation and engagement during the lesson. These findings suggest that slides designed for everyday contexts may be a strategic alternative for teaching Indonesian vocabulary to non-native speakers.